The Role of The Prosperous Justice Party (PKS) In the Implementation of Islamic Sharia Enforcement in the City of Banda Aceh - Nofriadi, Nofriadi; Sabnu, Alga; Qautsar, Muhammad Ilham; Siregar, Nurul Azizah; Nadila, Syarifa (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
This study explores the role of the Prosperous Justice Party (PKS) in promoting the implementation and strengthening of Islamic law (Sharia) in Banda Aceh City. As an Islamic-based political party with significant influence in the region, PKS actively directs government policies and programs to align with Islamic values. Through its members in the local legislative council (DPRK) and the Regional Oversight Faction, PKS promotes fair regulations, monitors the implementation of Sharia to prevent its misuse for political purposes, and ensures that all government agencies, not only the Department of Islamic Sharia, are involved in upholding Islamic principles. PKS also pays attention to criticism from women and non-Muslim groups, responding wisely while maintaining the spirit of Sharia as a social solution rather than a political symbol. Additionally, PKS conducts internal evaluations of its legislative members to uphold their commitment to Islamic values. The party also emphasizes cadre development, clean public services, and active community participation in policymaking to ensure that Sharia implementation remains relevant and adaptive to modern social dynamics.